1992
DOI: 10.1021/bi00121a018
|View full text |Cite
|
Sign up to set email alerts
|

Covalent modification and active site-directed inactivation of a low molecular weight phosphotyrosyl protein phosphatase

Abstract: Covalent modification experiments were conducted in order to identify active site residues of the 18-kDa cytoplasmic phosphotyrosyl protein phosphatases. The enzyme was inactivated by diethyl pyrocarbonate, phenylglyoxal, cyclohexanedione, iodoacetate, iodoacetamide, phenylarsine oxide, and certain epoxides in a manner consistent with the modification of active site residues. Phenylglyoxal and cyclohexanedione both bind to the active site in a rapid preequilibrium process and thus act as active site-directed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
56
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 53 publications
6
56
0
Order By: Relevance
“…Dicarbonyls may induce nonenzymatic modifications of various amino acids (Cys, Lys, or Arg) that are generally present in the putative active site of the receptor tyrosine kinase family (31). Some other hypothetical mechanisms potentially involved in dicarbonyl-induced EGFR inhibition have been excluded: 1) GO and MGO were not cytotoxic to cultured cells under the conditions used in the experiment; 2) the loss of EGFR activity was not associated with a loss of EGFR protein but rather resulted from a reduced specific activity of the EGFR kinase; 3) the GO/MGO-induced inhibition of EGFR phosphorylation does not result from activation of PTPases (involved in EGFR dephosphorylation) because, under our experimental conditions, GO/MGO strongly inhibited PTPases, in agreement with a previous report (32); and 4) GO/MGOinduced EGFR inhibition is not prevented by antioxidants such as ␣-tocopherol and N-acetyl-cysteine (data not shown).…”
Section: Discussionsupporting
confidence: 92%
“…Dicarbonyls may induce nonenzymatic modifications of various amino acids (Cys, Lys, or Arg) that are generally present in the putative active site of the receptor tyrosine kinase family (31). Some other hypothetical mechanisms potentially involved in dicarbonyl-induced EGFR inhibition have been excluded: 1) GO and MGO were not cytotoxic to cultured cells under the conditions used in the experiment; 2) the loss of EGFR activity was not associated with a loss of EGFR protein but rather resulted from a reduced specific activity of the EGFR kinase; 3) the GO/MGO-induced inhibition of EGFR phosphorylation does not result from activation of PTPases (involved in EGFR dephosphorylation) because, under our experimental conditions, GO/MGO strongly inhibited PTPases, in agreement with a previous report (32); and 4) GO/MGOinduced EGFR inhibition is not prevented by antioxidants such as ␣-tocopherol and N-acetyl-cysteine (data not shown).…”
Section: Discussionsupporting
confidence: 92%
“…For the deleterious action of methylglyoxal on the insulin signaling pathway, the decrease in tyrosine-phosphorylated IRS proteins was not due to impaired IRS synthesis/degradation as, after this short methylglyoxal treatment, IRS-1 protein levels were unchanged. Further, the reduction in IRS-1 tyrosine phosphorylation is not likely to be due to increased tyrosine dephosphorylation, as previous studies have reported a strong inhibition of phosphotyrosine phosphatases by ␣-ketoaldehydes (29,47). The decrease in insulin-stimulated phosphorylation of IRS-1 and IRS-2 (data not shown) on tyrosine was associated with a reduction in p85-IRS-1 association, PI3K activity, PKB activation, and hormone stimulation of glucose transport.…”
Section: Discussionsupporting
confidence: 59%
“…In fact, the reduced state of all the sulfhydryl groups of LMW-PTP has been demonstrated by our group and others (25,26). Both cysteines in positions 12 and 17 are conserved among the LMW-PTP subfamily, thus suggesting an important role for both residues.…”
Section: Regulation Of Lmw-ptp Activity On Pdgf Receptor Duringsupporting
confidence: 62%
“…We have already demonstrated that Cys-12 is the essential cysteine residue performing in the cysteinyl-phosphate intermediate during catalysis, whereas Cys-17 has a role in phosphate binding in cooperation with Arg-18 (27). Van Etten et al (26) have demonstrated that LMW-PTP has two reactive cysteines in the catalytic site with a low pK a (at pH 7.52 and 9.05 for iodoacetamide). Caselli et al (11,12) have demonstrated that H 2 O 2 and NO lead to the specific oxidation of Cys-12 and Cys-17 in the catalytic pocket of LMW-PTP.…”
Section: Regulation Of Lmw-ptp Activity On Pdgf Receptor Duringmentioning
confidence: 95%
See 1 more Smart Citation